2016
DOI: 10.1149/2.0751609jes
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Deformation Mechanisms of Composite Graphite Electrodes in Lithium-Ion Batteries

Abstract: Repeated charge and discharge of graphite composite electrodes in lithium-ion batteries cause cyclic volumetric changes in the electrodes, which lead to electrode degradation and capacity fade. In this work, we measure in situ the electrochemically-induced deformation of graphite composite electrodes. The deformation is divided into a reversible component and an irreversible component. Reversible expansion/contraction of the composite electrodes is correlated with localized changes in graphite layer spacing as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…The binder materials are used to be considered as an "inactive" component in the electrode; however, it has been widely recognized recently that the binder can play a significant role on the SEI formation on graphite electrode. [16][17][18][19][20] As for full cell, the capacity fade not only originates from cathode degradation but also stems from the SEI degradation on the graphite side. The SEI formation is critical for the graphite electrode; thick SEI film can significantly increase the resistance of the graphite electrode and result in fast capacity fade.…”
Section: Graphitementioning
confidence: 99%
See 1 more Smart Citation
“…The binder materials are used to be considered as an "inactive" component in the electrode; however, it has been widely recognized recently that the binder can play a significant role on the SEI formation on graphite electrode. [16][17][18][19][20] As for full cell, the capacity fade not only originates from cathode degradation but also stems from the SEI degradation on the graphite side. The SEI formation is critical for the graphite electrode; thick SEI film can significantly increase the resistance of the graphite electrode and result in fast capacity fade.…”
Section: Graphitementioning
confidence: 99%
“…A similar observation was also made by Jones et al and they suggested the irreversible capacity is closely related to the electrode deformation and binder with high stiffness can constrain the electrode deformation and help to form a thin SEI layer. [20] Another aqueous binder material, polyacrylic acid (PAA), has also been widely investigated. The abundant carboxyl groups along the PAA chain can have strong interaction with graphite particles via hydrogen bonding.…”
Section: Graphitementioning
confidence: 99%
“…This assumption is made to simplify the analysis and is motivated by the fact that only small volume changes have been reported due to the continuous change of the SEI layer with repeated electrochemical cycling after the first charge/discharge cycles. For refined damage models, the accumulation of SEI formation-induced stresses should be accounted for in future studies [40]. In Fig.…”
Section: Influence Of Residual Stresses On Internal Stressesmentioning
confidence: 99%
“…29 Binders such as PVDF influence the tensile strength of electrodes and adhesion strength of the active material to the current collector. 30 This is particularly important in systems with electrodes that undergo large dimensional changes. Li et al investigated the effect of the binder on electrode strain in Li-sulfur battery electrodes using a similar experimental set-up.…”
Section: Resultsmentioning
confidence: 99%